Konceptualne metafore sa sastavnicama život i smrt u Kamenom spavaču Maka Dizdara - Smlatić, Džemajla; Dolić, Belkisa (Književni jezik, 2021)
Conceptual metaphor is a cognitive mechanism often and gladly used in all discourse types, but it shows its maximum potentials in literature as it demystifies in an efficient and unique manner the experience, perception and mental schemas of a particular speaker – as both a member of a group and an individual. This paper analyzes the application of conceptual metaphorization in Mehmedalija Mak Dizdar’s Stone Sleeper with the concepts of life and death in the position of target domains with the aim of questioning its purpose, motivation and originality. The conceptual metaphors used in the collection are a clear reflection of the notion of human existence in the Bogumil spiritual tradition (the extremely negative intonation of the worldly and the rather positive intonation of the otherworldly reality) but, as it also turned out, in universal human thought. With each new insight into the motivic-thematic world of Dizdar’s poetics, its formal exceptionality and inexhaustibility of content are reaffirmed. This time, it was achieved using the apparatus of cognitive linguistics, i. e. by finding innovative metaphorical linguistic units expressing conventional conceptual metaphorization in Stone Sleeper.